Analysis of Green Building Implementation on the Additional Building of Universitas Swadaya Gunung Jati - Trianto Gustoro; Arya Ihcsan Alhafidin; Mohammad Dody Suyuti; Fathur Rohman Robandi (Pusat Publikasi Nusantara, 2025)
Environmental degradation and the rising energy demand in the building sector have underlined the urgency of implementing green building principles to mitigate ecological impacts and support long-term sustainability. This study aims to assess the sustainability performance of the Additional Building at Universitas Swadaya Gunung Jati using several evaluative parameters, including green open space, water efficiency, thermal comfort, lighting, carbon emission control, and energy performance. A quantitative-descriptive approach was employed using field measurements, direct observations, documentation, and verification interviews based on the Greenship Existing Building Version 1.1 standard issued by the Green Building Council Indonesia. The findings reveal that the building demonstrates strong compliance in terms of green open space (92.24%), optimal natural lighting (256.66 lux), and low OTTV values (16.91 W/m²), indicating efficient thermal resistance and minimal heat transfer through the building envelope. Conversely, water efficiency remains suboptimal due to the absence of alternative water management systems and roof tank infrastructure, leading to full reliance on electrical pumping. Thermal comfort also requires improvement since indoor temperatures and humidity exceed recommended benchmarks, which may influence user well-being and productivity. Overall, this study provides a comprehensive sustainability performance assessment and identifies key improvement indicators that can drive the development of a more energy-efficient and environmentally responsible campus. The results reinforce the strategic role of green building implementation in educational facilities as a foundation for future sustainable development.